Osrednje težave pri uporabi podatkovnih baz Evrokorpus in Evroterm - Petrović, Davor (Mostovi (Ljubljana), 2006)
The internet databases Evrokorpus and Evroterm are important tools for technical translators, especially due to their size, the professionalism of their compilers and the need for their regular updating. Many external translators are contributing terms, their translation equivalents and contexts, which is at the same time both the advantage and the drawback of the databases. Often too many translation equivalents are unnecessarily included, thus complicating work for translators.
Keywords: elektronski slovarji; Evrokorpus; Evroterm; korpusno jezikoslovje; slovenščina; spletni slovarji; terminološke zbirke